Bacteriological quality of dry powder milk available in local markets of Bangladesh - Afrin, Nazia; Shilpi, Rasheda Yasmin (Asian Journal of Medical and Biological Research, 2018)
Milk and milk powders are very rich in several nutrients and relished by everybody throughout the world. The present study was undertaken with the aim of investigating the bacteriological quality of locally available dry powder milk in Bangladesh. A total number of eight powder milk samples were collected from Gazipur city and its surrounding areas during the period from January 2017 to February 2017. The analysis comprised of enumeration of total viable bacterial count (TVBC), isolation of bacterial isolates and identification of pathogenic bacteria. Almost all the powder milk samples showed the total aerobic heterotrophic bacterial (TAHB) level above the standard acceptable range (>104 CFU/g). Both gram positive and gram negative pathogenic bacteria viz. Staphylococcus aureus, Staphylococcus epidermidis, Bacillus, pseudomonas sp. and Enterobacter sp. were isolated from studied samples through morphological and biochemical characteristics. Pseudomonas sp. were confirmed by API 20E. These results highlighted the necessity to maintain appropriate sanitary and hygienic measures at each critical point in order to safeguard consumers from food borne pathogens. Asian J. Med. Biol. Res. September 2018, 4(3): 267-273